Relationship between mental health and oral lesions: Recent evidence among university students (Research, Society and Development, 2026)
Introduction: The mental health of university students has been the subject of increasing attention, the increase in stress, anxiety, and depression among university students has direct repercussions on oral health due to neuroendocrine, immunological, and behavioral changes. This study aims to critically synthesize recent evidence regarding the relationship between mental health — with an emphasis on stress, anxiety, and depression — and oral lesions among university students, discussing their pathophysiological mechanisms, prevalence, clinical interactions, and implications for dental practice. Methodology: The present study consists of an integrative literature review, a method that enables the synthesis of evidence from studies with different methodological approaches. This design was chosen to allow a broad and multifactorial understanding of the relationship between mental health and oral lesions in university students. Results: There is a consistent association between psychological distress and oral manifestations in university students, especially temporomandibular disorders, bruxism, herpes simplex, and recurrent aphthous ulcers. These conditions result from stress-induced immunological and behavioral changes, with a negative impact on quality of life and academic performance. Discussion: Psychological distress among university students is directly associated with oral manifestations such as temporomandibular disorders, bruxism, herpes simplex, and recurrent aphthous ulcers. These findings reinforce the importance of early recognition and an interdisciplinary approach. Conclusion: It is concluded that stress, anxiety, and depression are strongly associated with oral manifestations in university students through biological and behavioral mechanisms. Early recognition of these alterations and an interdisciplinary approach are essential to promote comprehensive care and improve quality of life and academic performance.